2017
DOI: 10.3382/ps/pew225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of increasing levels of a microbial phytase in phosphorus deficient broiler diets via live broiler performance, tibia bone ash, apparent metabolizable energy, and amino acid digestibility

Abstract: The objective was to investigate increasing concentrations of an evolved microbial phytase on male broiler performance, tibia bone ash, AME, and amino acid digestibility when fed diets deficient in available phosphorus (aP). Experiment 1 evaluated the effects of phytase during a 21 d battery cage study and Experiment 2 was a 42 d grow-out. Experiment 1 included six treatments; negative control (NC) with an aP level of 0.23% (starter) and 0.19% (grower), two positive controls (PC) consisting of an additional 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
5
22
2
Order By: Relevance
“…Previous studies have shown that broilers fed diets supplemented with phytase improved P retention by 50-60% (Simons et al, 1990;Kornegay et al, 1996). Pieniazek et al (2016) reported that super dosing of phytase beyond the industrial level not only increase the P availability, but also the availability of other nutrients such as proteins, lipids, carbohydrates, Ca 2+ , Cu 2+ , and Zn 2+ as a result of elevated hydrolysis by phytase. Phytase also lowering the global feed industry cost by reducing the cost of nutritional inputs, for example, by replacing inorganic P sources such as dicalcium phosphate (DCP) (Mrigen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that broilers fed diets supplemented with phytase improved P retention by 50-60% (Simons et al, 1990;Kornegay et al, 1996). Pieniazek et al (2016) reported that super dosing of phytase beyond the industrial level not only increase the P availability, but also the availability of other nutrients such as proteins, lipids, carbohydrates, Ca 2+ , Cu 2+ , and Zn 2+ as a result of elevated hydrolysis by phytase. Phytase also lowering the global feed industry cost by reducing the cost of nutritional inputs, for example, by replacing inorganic P sources such as dicalcium phosphate (DCP) (Mrigen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been investigated to improve available PP utilization. Supplementations of low P diets with phytase have been shown to improve dietary P digestibility in sows ( Torrallardona et al., 2012 , Sands et al., 2001 ) and broilers ( Jiang et al., 2013 , Pieniazek et al., 2017 , Woyengo et al., 2010 , Ravindran et al., 2006 ). Consistently, Pillai et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, 1995 broilers in the rye–corn group had stronger tibias than those birds fed rye in the second phase of the experiment indicating some recovery in bone strength has occurred. Tibia bone ash improved when a low phosphorus diets were supplemented with phytase, suggesting that the enzyme increased mineral availability ( 62 ). Therefore, it likely that switching from a rye to a corn-based diet increased mineral availability allowing for improved bone quality in modern and 1995 broilers.…”
Section: Discussionmentioning
confidence: 99%